PERKEMBANGAN GONAD IKAN SIDAT (Anguilla marmorata) DI DANAU POSO [Gonads development of eels (Anguilla marmorata) in Lake Poso] - Gadis Sri Haryani; Lukman Lukman; Triyanto Triyanto (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2008)
The gonads condition of eels (Anguilla marmorata) in Lake Poso was studied. The aim of this research is to identify gonads development of eel in Lake Poso and estuary of Poso River. Based on histological analyses of the gonad, eels collected in the Lake Poso and in the estuary were in the early vitellogenic stage, and the GSI (Gonadosomatic index) value ranged between 0.60 -4.40%. Development stage of female gonads showed four stages: chromatin nucleolar, perinucleolar, cortical alveoli and vitellogenic. The male gonads showed only pre-spermatogenic stage which contains only spermatogonia. Next stages should be reached during down stream migration to the deep sea.